Neighborhood Satisfaction: A Study of a Low-Income Urban Community. Issue 6 (November 2019) - Ciorici, Patricia; Dantzler, Prentiss
This article discusses the findings from a study on neighborhood satisfaction conducted within the North Camden neighborhood context. Using data from the 2011 North Camden Resident Satisfaction Survey, the study examined the subjective measures of neighborhood-level characteristics to identify the determinants of neighborhood satisfaction. A binary logistic regression analysis revealed that the quality of social networks, neighborhood physical conditions, neighborhood safety, and quality of public services are positively associated with neighborhood satisfaction. Surprisingly, the analysis showed that the extent of social networks and access to transportation have an inverse relationship with the satisfaction of residents with their neighborhood. The article discusses these findings and the way in which the results can inform practitioners about policies and programs that need to be developed and implemented to improve neighborhood satisfaction and, ultimately, individual and community well-being.